1987
DOI: 10.1016/0014-5793(87)81242-5
|View full text |Cite
|
Sign up to set email alerts
|

EPR redox study of cytochrome c3 from Desulfovibrio vulgaris Miyazaki

Abstract: We report the results of an EPR potentiometric titration of cytochrome c3 from DesulJbvibrio vulgaris Miyazaki: the EPR spectral features of the four hemes are identified. The four midpoint redox potentials, which are deduced from the integrated intensity variations as a function of the redox potential, are within the range -230 to -360 mV with two nearly equal intermediate values, in agreement with previous electrochemical measurements. A structural change of the environment of the heme with the most negative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
18
1

Year Published

1989
1989
2005
2005

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 19 publications
1
18
1
Order By: Relevance
“…Modifications of the method have been introduced to take into account the existence in the oxidized state of two distinct conformational states for heme 4 and their interconversion which occurs when heme 1 is reduced. As expected from our previous work [6], we found that, as in DdNc3, the redox interactions are moderate, with absolute values less than 25 mV. Our results disagree with an earlier interpretation of electrochemical measurements on DvMc3 in which two hemes were thought to be equivalent and independent of the other two hemes [9].…”
contrasting
confidence: 76%
See 3 more Smart Citations
“…Modifications of the method have been introduced to take into account the existence in the oxidized state of two distinct conformational states for heme 4 and their interconversion which occurs when heme 1 is reduced. As expected from our previous work [6], we found that, as in DdNc3, the redox interactions are moderate, with absolute values less than 25 mV. Our results disagree with an earlier interpretation of electrochemical measurements on DvMc3 in which two hemes were thought to be equivalent and independent of the other two hemes [9].…”
contrasting
confidence: 76%
“…Spectral modifications of heme 4 are also observed during the redox titration of DvMc3 [6]. However the situation is more complicated in the present case.…”
Section: Measurements Of the Redox Parametersmentioning
confidence: 58%
See 2 more Smart Citations
“…The site-specific heme assignments were also.supported by NOE between the methyl groups of these hemes and the side chain ofVaP s. All the results contradicted the.heme assignments for D.v. MF cytochrome c3 made on the basis of electron spin resonance (Gayda et al (1987) FEBS Lett., 217 57-61). Based on these assignments, the interaction of cytochrome c3 with D.v.…”
mentioning
confidence: 99%